Myelodysplastic syndrome patients present more severe respiratory muscle impairment and reduced forced vital capacity: Is disordered inflammatory signaling the culprit? - Bruno Memória Okubo; Anacélia Gomes de Matos; Howard Lopes Ribeiro Junior; Daniela de Paula Borges; Roberta Taiane Germano de Oliveira; Marilena Facundo de Castro; Manoel Ricardo Alves Martins; Romélia Pinheiro Gonçalves; Pedro Felipe Carvalhedo Bruin; Ronald Feitosa Pinheiro; Silvia Maria Meira Magalhães (PLoS ONE)
Background/objectives The ageing process is associated with gradual decline in respiratory system performance. Anemia is highly prevalent among older adults and usually associated with adverse outcomes. Myelodysplastic syndromes (MDS) are a heterogeneous group of hematologic malignancies with increasing incidence with age and characterized by anemia and other cytopenias. The main objectives of this study were to evaluate respiratory muscle strength and lung function in elderly patients with anemia, compare data between myelodysplastic syndromes and non-clonal anemias and evaluate the influence of serum IL-8 level and NF-kB activity on deteriorate pulmonary function in this specific population. Participants Individuals aged 60 and older with anemia secondary to MDS, non-clonal anemia and healthy elderly individuals. Measurements Forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and FEV1/ FVC ratio were measured by spirometry. Respiratory muscle strength was evaluated by maximal static respiratory pressures measurement. IL-8 analysis was performed by ELISA and activity of NF-kB by chemiluminescent assay. Results Mean Hb concentration was comparable between patients with anemia. Significant differences were detected between all patients with anemia and controls for maximum-effort inspiratory mouth pressure (PImax) and also for maximum-effort expiratory mouth pressure (PEmax). The MDS group recorded a significantly lower PImax and PEmax percent predicted when compared to non-clonal anemia group. For FVC and FEV1, a significant difference was found in anemic patients, with even significantly lower values for FVC and FEV1 in MDS group. No significant differences were detected for PImax and PEmax and spirometry parameters when anemic patients were stratified according to the degree of anemia. A significant negative impact in FVC (% pred), PImax (% pred) and PEmax (% pred) was observed in patients with MDS and higher levels of IL-8 or increased activity of NF-kB. Conclusion A negative impact of anemia, independent of its degree, was demonstrated in respiratory muscle strength and lung function particularly in MDS. The well known elevated proinflammatory cytokines in MDS patients were proposed to play a role as was demonstrated by detrimental effect of higher IL-8 and NF-kB in pulmonary function tests in this population.